A Biogas Desulphurization System with Water Scrubbing - Lien, Cheng-Chang; Lin, Wei-Cheng (Advances in Technology Innovation, 2019)
The biogas is renewable energy with very good potential. It is a gas produced by the bacteria transformation of the organic substance under the anaerobic condition. It is a flammable gas because it contains the hydrogen sulfide (H2S) in its composition. It will cause damage to metal equipment and the corrosion of the pipe. So before using the biogas, the desulphurization process should be carried on. The purpose of this study was to design a water scrubbing system for biogas and carry on the performance test of the desulphurization process in the hog farm. In the field test, the biogas flow rate is changed in the water scrubbing cylinder and under different external circulation water flow rate. The H2S concentration in the biogas is detected before and after water scrubbing, and the desulphurization efficiency of biogas was discussed, furthermore, the pH value of water in the water storage tank was measured. When the H2S adsorbed by water was at steady state, whether the pH value of external circulation water can meet the effluent standard was discussed. From the test results, it showed that the removal efficiency of H2S was 47.7% in 30 minutes of water scrubbing time under 120 ℓ of total water amount, 80 cm of water level in the water scrubbing cylinder, 20 ℓ/min of internal circulation water flow rate and 10 ℓ/min of external circulation water flow rate, and 25 ℓ/min of biogas flow rate. The pH value of water in the water storage tank was 6.22, which met the effluent standard of regulation for discharging directly. This system can reduce the H2S content in the biogas, and purify the quality of the biogas. The operation of this system is convenient and the fabrication cost is low, which is suitable for the small-scale hog farm to purify the biogas.